Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Melalui Semangat Kerja pada Bank di Surabaya : Tinjauan Literatur Sistematis - Achmad Zaki Fadhil (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to synthesize empirical evidence on the influence of leadership style and organizational culture on employee performance, with a focus on the mediating role of work engagement in the banking industry context. Using the Systematic Literature Review (SLR) method, the literature search was conducted across various databases using strict inclusion-exclusion criteria. Out of 69 identified records, 7 relevant original studies were successfully included. The results of the qualitative synthesis indicate a strong consensus that effective leadership styles and supportive organizational cultures positively and significantly affect employee performance, and this effect is largely mediated by work engagement. Work engagement has been shown to be a key mechanism that translates management practices into optimal performance outcomes. Descriptive quantitative analysis shows that the majority of studies use the SEM method and find both full mediation and partial mediation. These findings provide practical implications for bank management in Surabaya to prioritize strategies for enhancing work enthusiasm as a strategic investment to drive performance.